3(x+2)+4(5-x)=

Simple and best practice solution for 3(x+2)+4(5-x)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+2)+4(5-x)= equation:


Simplifying
3(x + 2) + 4(5 + -1x) = 0

Reorder the terms:
3(2 + x) + 4(5 + -1x) = 0
(2 * 3 + x * 3) + 4(5 + -1x) = 0
(6 + 3x) + 4(5 + -1x) = 0
6 + 3x + (5 * 4 + -1x * 4) = 0
6 + 3x + (20 + -4x) = 0

Reorder the terms:
6 + 20 + 3x + -4x = 0

Combine like terms: 6 + 20 = 26
26 + 3x + -4x = 0

Combine like terms: 3x + -4x = -1x
26 + -1x = 0

Solving
26 + -1x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-26' to each side of the equation.
26 + -26 + -1x = 0 + -26

Combine like terms: 26 + -26 = 0
0 + -1x = 0 + -26
-1x = 0 + -26

Combine like terms: 0 + -26 = -26
-1x = -26

Divide each side by '-1'.
x = 26

Simplifying
x = 26

See similar equations:

| 9-t-3(t-3)=0 | | 8+3(4n+6)-n= | | 4x+22=18 | | 7+3g=3+7g | | 30=2(10+y) | | ln(x-6)=3 | | 16a^4+4a^3b-6a^2b^2=0 | | 8x+9=5x+11 | | 3logx+6=0 | | 9t^3+12t^2-45t=0 | | 152+2h=1040 | | 60x^9y^7-36x^6y^5+36x^3y^2= | | 5-7=0 | | y^2-3y-130=0 | | -8q+6+5q-3=0 | | 850=5(x+18) | | 2x-12=6x+7 | | 9x(2x-7)= | | 3x^2+y+3z^2=0 | | 4(X-7)=4x-12 | | x+(x*.2625)-14026=0 | | x^2+5x+4x+20=0 | | 9b+13=15b-5 | | 8+4(2n+3)-n= | | a^5-18a=7a^3 | | 6x-16x+4=38x | | -2(v+4)=6v-6+3(2v+2) | | 12x^4+60x^3+27x^2=0 | | 3(6x+2)+6(4x+6)+3=42x+46 | | 0.2x+0.1=0.4x-1.5 | | 4*10+15= | | 2x^2-3x+35=0 |

Equations solver categories